Toward a slow criminology of sociotechnical orderings: A tale of many youth repellents - Savoie, Patrick (Theoretical criminology, 2019)
Taking the material turn can contribute to renewing the discipline and sustaining the development of a slow criminology. Treating objects as mediators and acknowledging their ontological multiplicities protect us from our reflex to condemn rather than analyze them. Using the example of the ‘youth repellent', we document three of its instantiations: a spatial fluidity device; a pain delivery mechanism; and an environmental pollution agent. This exploration forces us to expand the borders of the discipline to embrace others such as audiology and epidemiology. While these detours slow our analysis, they are the price we must pay for doing justice to the messiness of the human and non-human associations that constitute the fabric of our world.